Urbanizing Peripheries: An aspect based study of urban fringes in the region around Pune city to understand its character and pattern of development - Hrishikesh Ashtekar, Devendra Deshpande, Garima Buraghoain (International Journal of Advanced Science and Technology, 2020)
Urban sprawl, the word used for the built environment in urban fringes connotes negatively to the overlap of new development patterns over the surrounding villages, farmlands and natural resources. Usually under planning processes, common development guidelines are formulated for the market driven development. In this process, urban character, alien to the social and cultural context of existing situations gets generated that disrupts their image and identity. Through last three years of design studios, an aspect based method of reading, understanding and analyzing the urban peripheries of Pune region, which is a radial growing urban area with many of the villages and towns surrounding it getting engulfed in the urban agglomeration, thus becoming satellite or suburbs of the larger city. Each of these town or village in the peripheries has its own unique identity and way of life. This paper puts forth methods which are both observational as well as people participative, carried out by students of 4th year B.Arch. It also comes up with a methodology to draw up commonalities and variations which are unique to each of the areas due to their cultural and geomorphologic differences. The intention of the paper is to put forth a methodology of developing understanding of an area in terms of its existing character, social amenities, public utilities, physical infrastructure, open spaces, cultural background etc. This understanding can serve as a base for any kind of the bureaucratic planning processes like town planning schemes, local area planning in the urban fringes. It can also put forth the ‘Specific profile’ of different fringe areas of the city that can help the people living there to be aware of the positives as well as negatives of their urban areas in terms of available urban resources. It may also help them specifically to identify their needs and requirements in future for basic amenities, physical infrastructure, social infrastructure, open spaces etc.